In situ growth of porphyrinic metal–organic framework nanocrystals on graphene nanoribbons for the electrocatalytic oxidation of nitrite - Kung, Chung-Wei; Li, Yan-Sheng; Lee, Min-Han; Wang, Shan-Yu; Chiang, Wei-Hung; Ho, Kuo-Chuan (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
Graphene nanoribbons (GNRs) are incorporated with the nanocrystals of a porphyrinic metal–organic framework, MOF-525 , by solvothermally growing MOF-525 in a suspension of well-dispersed GNRs. A nanocomposite, which is composed of the MOF-525 nanocrystals interconnected by numerous one-dimensional GNRs, is successfully synthesized. Due to the excellent dispersity, uniform thin films of the MOF-525 /GNR nanocomposite can be simply deposited on conducting glass substrates by using drop casting. The obtained thin film of the MOF-525 /GNR nanocomposite is applied for electrochemical nitrite sensors. The MOF-525 nanocrystals serve as a high-surface-area electrocatalyst toward nitrite and the interconnected GNRs act as conductive bridges to provide facile charge transport. The thin film of the MOF-525 /GNR nanocomposite thus exhibits a much better electrocatalytic activity for the oxidation of nitrite compared to the pristine MOF-525 thin film.